АНГЛИЧАН ҲӘМ ҚАРАҚАЛПАҚ ФОЛЬКЛОРЫНДА ЕРТЕКЛЕРДИҢ ӘДЕБИЙ ЖАНР СЫПАТЫНДА КӘЛИПЛЕСИЎИНИҢ САЛЫСТЫРМАЛЫ ҮЙРЕНИЛИЎИНДЕГИ АЙЫРЫМ МӘСЕЛЕЛЕР - Сайтова, З. (FAN va JAMIYAT, 2016)
The article deals with the comparative study of English and Karakalpak folk tales. In the article the author analyses the plot and composition of folk tales of these two different peoples, paying a proper attention to the main characters in tales. There have been emphasized some specific typological pecularities and similarities in their composition and ideological contents of fairy tales of these two different cultures.